CONSTRUCTIVISM APPROACH TO DEVELOP STUDENTS’ CRITICAL THINKING FOR WRITING ANALYTICAL EXPOSITION TEXT - Sharizan, Sharizan; Titania, Fani Nabila; Handayani, Riris; Hidayah, Ayu Rahmah (ENGLISH JOURNAL, 2025)
This research examines the use of the constructivism approach to develop students’ critical thinking for writing analytical exposition texts. This notion appears as the response to the student’s problem in constructing analytical exposition text critically. The primary resources of this literature review research are written and spoken literature. This study explains the foundation of constructivism approach to develop students’ critical thinking for writing analytical exposition texts. According to the discussion of this literature research, the constructivism approach can be used to create essential thinking since it lets the students construct knowledge by themselves from natural and contextual experiences in the field. That is why the constructivist approach has the potential to develop students’ critical thinking while writing analytical exposition texts. However, teachers and students should understand this approach, especially in implementing it, to maximize the use of constructivism for developing critical thinking in writing analytical exposition texts.